PENGGUNAAN MEDIA BENDA KONKRET UNTUK MENINGKATKAN PEMAHAMAN SISWA DALAM PEMBELAJARAN MATEMATIKA TENTANG BILANGAN 1 SAMPAI DENGAN 1000 PADA SISWA KELAS II SDN 02 MADIUN LOR KECAMATAN MANGUHARJO - Khoiriyah, Ajeng Estu; Sri Lestari; Rita Rahmadhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Mathematics is a main subject contained in every curriculum. Understanding Mathematics lessons is very necessary. Based on observations that have been made, it was found that class II students at SDN 02 Madiun Lor, Manguharjo District had difficulty understanding mathematics lessons about the numbers 1 to 1000, because the learning carried out was rigid and less flexible, the teacher only used the lecture method and adhered to the textbook without paying attention. other factors that influence students' activeness in learning mathematics. This has an impact on low student learning outcomes. So media is needed that can be used to increase students' understanding. This research is classroom action research (CAR). Classroom action research is research conducted to overcome problems in the classroom. Classroom action research can be used as a means for teachers to improve the quality of learning effectively. This research was conducted to determine the increase in students' understanding by using concrete object media in mathematics learning about numbers 1 to 1000 in class II students at SDN 02 Madiun Lor, Manguharjo District.